Examining the process and the outcomes of a 12-month learning journey of intercollegiate sport coaches accompanied by a personal learning coach - Rodrigue, F. (2019)
The purpose of this doctoral dissertation was to advance the scientific knowledge on the development of high-performance coaches by proposing a new developmental approach to help intercollegiate sport coaches learn from their coaching practice. When applied to coach development, the theory of lifelong learning(Jarvis, 2006) suggests that coach learning evolves with the coaches`experiences and developsfrom participating inthe environment. However, current development opportunities for high-performance coaches lack connection with practice and forego reflective practice. This lead researcherthus set out to undertake a 12-month action research operationalised using appreciative inquiry to accompany intercollegiate sportcoaches along their learning journey. A personal learning coach accompanied five intercollegiate sport coaches using narrative-collaborative coaching(NCC)to create a safe space for them to reflect. The findings are presented across four articles. The first article suggested reflective cards as a useful tool for coaches to engage in reflective practice. Findings from Article One also presented a model for other coaches to reflect on theircoachingpractice.Article Two described the main components of NCC, which was used by the personal learning coach to create a safe reflective space. Astep-by-step methodology for using appreciative inquiry is presented. In Article Three, data generated from the journey of a female high-performance women`s rugby coach was used to extend the definition of a personal learning coach and to compare theroleof PLCwith other coach development actors. Findings about the evolution and the value creation of the accompanied learning journeyare also presented. Article Four shared results specific to the intercollegiate context with the presentation of the companionship between a PLC and two intercollegiate ice hockey head coaches. These collaborative partnerships led to unique learning journeys, and created valuable learning activities within complex value creation stories. The four articles together make novel theoretical and practical contributions to the field of coach development by presenting a new developmental approach to accompany coach learning and by introducing an analytical framework to evaluate the value of learning activities